Sign‐Supported English: is it effective at teaching vocabulary to young children with English as an Additional Language?. Issue 5 (26th February 2015) - Marshall, Chloë R.; Hobsbaum, Angela
Abstract Background Children who are learning English as an Additional Language (EAL) may start school with smaller vocabularies than their monolingual peers. Given the links between vocabulary and academic achievement, it is important to evaluate interventions that are designed to support vocabulary learning in this group of children. Aims To evaluate an intervention, namely Sign‐Supported English (SSE), which uses conventionalized manual gestures alongside spoken words to support the learning of English vocabulary by children with EAL. Specifically, the paper investigates whether SSE has a positive impact on Reception class children's vocabulary development over and above English‐only input, as measured over a 6‐month period. Methods & Procedures A total of 104 children aged 4–5 years were recruited from two neighbouring schools in a borough of Outer London. A subset of 66 had EAL. In one school, the teachers used SSE, and in the other school they did not. Pupils in each school were tested at two time points (the beginning of terms 1 and 3) using three different assessments of vocabulary. Classroom‐based observations of the teachers' and pupils' manual communication were also carried out. Outcomes & Results Results of the vocabulary assessments revealed that using SSE had no effect on how well children with EAL learnt English vocabulary: EAL pupils from the SSE school did not learn more words than EAL pupils at the comparison school. SSE was used in almost half of the teachers' observations in the SSE school, while spontaneous gestures were used with similar frequency by teachers in the comparison school. Conclusions & Implications There are alternative explanations for the results. The first is that the use of signs alongside spoken English does not help EAL children of this age to learn words. Alternatively, SSE does have an effect, but we were unable to detect it because (1) teachers in the comparison school used very rich natural gesture and/or (2) teachers in the SSE school did not know enough BSL and this inhibited their use of spontaneous gesture. Explanations (1) and (2) might mean that the potential benefits of spontaneous gesture in the input to the children in the comparison school matched any potential benefits of SSE. We suggest that studying early years professionals' spontaneous use of gesture, and how their gesture supports the language learning of all children in their class, would be fruitful areas of research for the future.